2018
DOI: 10.1038/s42004-018-0090-3
|View full text |Cite
|
Sign up to set email alerts
|

A tunable lanthanide cubane platform incorporating air-stable radical ligands for enhanced magnetic communication

Abstract: The unique properties of polynuclear cluster-aggregates have long been staples in the molecular magnetism community. The initial success observed in high nuclearity transition metal complexes for generating exciting magnetic behaviors however, has not yet fully been extended to lanthanide-based clusters. This is in part due to the challenges related to promoting non-negligible magnetic interactions between two lanthanide ions. One promising route towards improving magnetic communication involves the incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 58 publications
3
31
1
1
Order By: Relevance
“…With this in mind, we sought to investigate the effect of such groups on their magnetic behaviour, with a focus on complexes based on non‐Kramers ions, such as Tb 2 SMMs. Our recent work in this regard has shown that the stabilisation of ground Kramers doublet and the reorientation of the magnetic anisotropy axes can lead to significant improvements in the energy barrier ( U eff ) . In doing so, we are able to identify the key points for a design strategy that optimises the performance of the complex from both a magnetic and optical perspective.…”
Section: Resultsmentioning
confidence: 98%
“…With this in mind, we sought to investigate the effect of such groups on their magnetic behaviour, with a focus on complexes based on non‐Kramers ions, such as Tb 2 SMMs. Our recent work in this regard has shown that the stabilisation of ground Kramers doublet and the reorientation of the magnetic anisotropy axes can lead to significant improvements in the energy barrier ( U eff ) . In doing so, we are able to identify the key points for a design strategy that optimises the performance of the complex from both a magnetic and optical perspective.…”
Section: Resultsmentioning
confidence: 98%
“…Aus präparativer Sicht ist es recht anspruchsvoll, die oben erwähnten Strategien bei der Optimierung von SMM‐Eigenschaften zu verfolgen, besonders bei Komplexen mit einer Nuklearität >2, bei denen die Steuerung der Symmetrie und der magnetischen Axialität schwierig sein kann. Viele neuere Entwicklungen konzentrieren sich auf die Einführung von Radikalliganden in Metallkomplexe (Abbildung 3), die sogar mit Lanthanoiden stärkere magnetische Wechselwirkungen hervorrufen können [72–82] . Dies ist darauf zurückzuführen, dass Radikale die tief verdeckten 4f‐Orbitale besser erreichen können, wodurch eine direkte Austauschkopplung zwischen dem Lanthanoid und dem Radikalliganden ermöglicht wird.…”
Section: Fortschritte Auf Dem Gebiet Der Einzelmolekülmagneteunclassified
“…In addition, this strategy could potentially enable the investigation of magnetic entanglemente ffectsb etween two lanthanide ions mediated by redox-active ligands. [32][33][34][35] Along the same lines, the redoxcontrolled encapsulation of different guest molecules could also play ak ey role in defining the magneticc haracteristics of the complex.…”
Section: Introductionmentioning
confidence: 99%
“…The prominence of such molecular arrangements is closely tied to Stoddart's achievements in the field of molecular machines andm echanicallyi nterlocked molecules. [43,44] Buildingu pon our previousa chievements on air-stable radical-bridged complexes forp robingm agnetic exchange interactions, [34,45,46] we sought to devise as eries of functional metalorganic architecturesi ncorporating stimuli-responsiveo rganic linkers displaying at least two accessible/stable redox states. Our efforts have focusedo n1 ,1'-bis(4-carboxyphenyl)-(4,4'-bipyridinium) dichloride (H 2 bcbp•2Cl), which features two coordinating carboxylate moieties at each end of the molecule, to promote either the formation of high dimensionality coordination networks or extended nanocapsules upon metal coordination.…”
Section: Introductionmentioning
confidence: 99%